PENGARUH PERFORMANCE QUALITY TERHADAP ORGANIZATIONAL COMMITMENT FRONTLINE EMPLOYEE - sri Vandayuli Riorini (Media Riset Bisnis & Manajemen, 2004)
Performance quality of frontline employees is a very important aspect that needs hypothesis into consideration by service industry because they have direct contact with consumers. The level of quality performance of frontline employees can determine their level of commitment towards the company. The objective of this research is to identify the effect of performance quality to organizational commitment of frontline employees. Respondents being used for this research are frontline employees of private banks, namely tellers and customer services. Data is analyzed using Multiple Regression Analysis. The result of this research can provide implication for managers to maintain continous commitment from their frontline employees. Suggestion for further research is to conduct similar research on different service industries and other frontline employees.